What are Deep Disagreements? - Arroyo, Gustavo J. (Informal Logic, 2024)
The scholarship on deep disagreements presents us with a considerable number of seemingly disparate characterizations concerning the nature of these disputes. This paper is motivated by the desire to grasp what these characterizations are. An answer is provided through the method of reconstructive analysis. Two ideal and paradigmatic models of deep disagreements are defined initially. Then, individual characterizations found in the scholarship are examined against the background of such models. Special attention is given to Fogelin’s paper, the work that initiates modern discussion on deep disagreements. According to the interpretation provided in the following paper, both models inadvertently coexist in this seminal work.